Service user involvement in mental health service commissioning, development and delivery: A systematic review of service level outcomes - Naseeb Ezaydi; Elena Sheldon; Alex Kenny; Elizabeth Taylor Buck; Scott Weich (Wiley, 2023)
Abstract Introduction Service user involvement is increasingly considered essential in mental health service development and delivery. However, the impact of this involvement on services is not well documented. We aimed to understand how user involvement shapes service commissioning, development and delivery, and if/how this leads to improved service‐level outcomes. Methods A systematic review of electronic databases (MEDLINE, PsycINFO, CINAHL and EMBASE databases) was undertaken in June and November 2022 for studies that incorporated patient involvement in service development, and reported service‐level outcomes. Included studies were synthesised into a logic model based on inputs (method of involvement), activities (changes to service) and outputs (indicators of improvement). PRISMA (Preferred Reporting Items for Systematic Reviews and Meta‐Analysis) guidelines were followed when conducting this review. Results From 10,901 records identified, nine studies were included, of which six were judged to have used co‐production or co‐design approaches. Included studies described service user involvement ranging from consultation to co‐production. We identified a range of outputs associated with service user involvement in service planning and delivery, and reported these in the form of a logic model. These service‐level outputs included improved treatment accessibility, increased referrals and greater service user satisfaction. Longer‐term outcomes were rarely reported and hence it was difficult to establish whether outputs are sustained. Conclusion More extensive forms of involvement, namely, co‐design and co‐production, were associated with more positive and substantial outputs in regard to service effectiveness than more limited involvement methods. However, lived experience contributions highlighted service perception outputs may be valued more highly by service users than professionals and therefore should be considered equally important when evaluating service user involvement. Although evidence of longer term outcomes was scarce, meaningful involvement of service users in service planning and delivery appeared to improve the quality of mental health services. Patient or Public Contribution Members of a lived experience advisory panel contributed to the review findings, which were co‐authored by a peer researcher. Review findings were also presented to stakeholders including service users and mental health professionals.